PENGARUH FLUKTUASI SALINITAS TERHADAP NITRIFIKASI OLEH BAKTERI YANG DIAMBIL PADA ESTUARI SUNGAI BANJIR KANAL BARAT – SEMARANG - Maulina Harsitoningrum (Jurnal Teknik Lingkungan, 2013)
Many marine environmental pollution caused by industrial waste content comes from a variety of human activities is increasingly rising. Salinity, nitrogen and high phosphate present in industrial waste discharged directly and will cause damage to the receiving water bodiesHigh content of nutrients that will cause water pollution in the ecosystem. Presence of phosphate in the water will cause eutrophication. With a highly eutrophic conditions allow for the rapid growth of algae (bloom) due to the availability of excess phosphate.In this research, sampling location of the research team selected one is where the results are Sea Canal River West Flood Canal. Sea Canal River West Flood Canal has characteristics that can be seen from the test results of baseline characteristics by using a tool such as the Water Quality Cheker namely: temperature, pH, salinity, turbidity (NTU), Dissolved Oxygen (Dissolved Oxygen), and TDSThe study was conducted by observing the fluctuations in salinity that occur in nitrification by bacteria in each reactor. NH4 +-N using NH4Cl is also a necessary nutrient for bacterial nitrification. Salt water is added varying levels are: 0%, 0,5%, 1,5%, 3%, 5%, and 7%.